Efficacy of oral fluconazole in the treatment of seborrheic dermatitis: A placebo-controlled study - BEKİROĞLU, GÜLNAZ NURAL; ERGUN, SAFİYE ATLAS TÜLİN (My University, 2007)
Background: Seborrheic dermatitis (SD) is a common, chronic dermatosis. Although the pathogenetic mechanisms of SD are not clear, Malassezia spp. yeasts are known to cause the disease. Previous studies have shown that topical and systemic antifungals provide clinical benefit. Objective: To evaluate the safety and efficacy of short-term oral fluconazole in patients with SD. Methods: Sixty-three patients with mild-to-moderate SD were randomly allocated to receive either oral fluconazole 300mg in a single dose per week or placebo, for 2 weeks. Twenty-seven patients taking fluconazole and 23 patients taking placebo completed the study and were analyzed. The SD area severity index (SDASI) score and the patient' subjective assessment of pruritus and burning sensation were evaluated before and after treatment. Both the investigator and the patients were blinded to treatment. Results: A statistically significant improvement in SDASI score after treatment compared with baseline was obtained with fluconazole (p = 0.01) but not with placebo. However, the difference between the treatment groups was not statistically significant (p > 0.05). Subjective improvements in symptoms, such as pruritus and burning sensation, were observed in both groups but no statistically significant differences versus baseline were seen. Conclusion: The results of this study indicate that fluconazole provides marginal and statistically insignificant benefit for the therapy of SD. However, larger studies using different dosages and/or durations of fluconazole therapy may provide a rationale for systemic use of fluconazole in SD. © 2007 Adis Data Information BV. All rights reserved.